The spring suspension of a rolling stock providing safety impovement and increase of running speed - Y. F. Saveliev; V. Y. Shevchenko; N. Y. Simak (Вестник СибАДИ, 2017)
The article dwells upon generalizing researches’ results of a condition of modern and standard spring suspension of railway carriages. On the basis of operation’s experience of domestic and foreign rolling stock there is drawn a conclusion on need of modernization of its spring suspension in modern conditions. The authors present new fundamental constructive diagrams of vibroprotection devices for various types of a rolling stock.